O cidadão eleitor: crimes eleitorais e afirmação da cidadania - Mello, Adriana Marenco Dumans e (2014)
The research paper titled "The voter: electoral crimes and affirmation of citizenship" has the scope of the examination of the democratic environment of the country , especially the elements of sanitation of citizenship. Brings better understanding about the current normative design of criminalization of conduct by the Election Penal Law, in its aspects concerning the affirmation of citizenship, main objective of the research line that binds the present study, considered as an instrument of ensuring the legitimacy of the electoral process. The research is aimed to check the instruments that act to strengthen citizenship by voting in an electoral field that confers very high level of competitiveness, challenged by several elements considered "pollutants", both between and among the electorate candidates what does not dispense treatment by the sanction of the components that could compromise the fairness and honesty of elections. From this perspective, topping the criminal offense of legal rights protected by the Electoral Law, which justifies the legal provision of electoral crimes, seeking to inhibit and suppress behaviors that offend democracy and citizenship by voting. The research and considerations that we propose to develop (this time without the quality of originality), seeking to focus these regulatory provisions and their relevance in the affirmation of citizenship. Our proposal passes, initially, the objective appro ach of political representation through voting, as an instrument of democratic citizenship and affirmation for, after analyzing criminal behavior polluting the political process through classification and analysis of specific types of Criminal Electoral Law.